Ablehnungs- und Umsetzungsraten von Organtransplantationen - mögliche Ursachen und denkbare Auswege Eine empirische Datenanalyse aller im Jahr 2013 im Kantonsspital St. Gallen verstorbener Patienten - Pfyffer von Altishofen, Monika (sui generis Verlag, 2021)
The work deals intensively with the very complex topic of post-mortem organ donation and the question of why it is that not all organs of potential organ donors are considered in transplantation. It covers central questions of the legally and ethically required handling of dying and death. In addition to a presentation of the relevant legal situation, the statistical findings on organ transplants performed in Switzerland during the observation period, the relatively high rates of rejection and low rates of conversion of organ donations by means of retrospective analysis of the data of all in 2013 at their then place of work, the Cantonal Hospital of St. Gallen are made and their results compared with those of the national SwissPOD study. The "primary desirable goal" of the measures taken to promote organ donation appears to the author to be less the "increase in available organs, but rather reflection on dying and one's own death", which is why she would welcome an increase in the number of living wills and organ donation cards available, in order to thereby reduce the emotionally stressful proxy decisions - regardless of the will specified therein.